Kedudukan Pewarisan Tanah Pauseang oleh Anak Perempuan pada Masyarakat Adat Batak Toba Pasca Perceraian - Olivia Cherie Comeito (Notaire, 2026)
Within the cultural framework of the Toba Batak indigenous community, which adheres to a strict patrilineal kinship system, “perkawinan jujur” constitutes a vital customary obligation involving the full provision of “uang jujur” from the male relatives to the woman. Upon completion of this provision, the pauseang land is bestowed by the parents to their daughter as a marriage dowry through a customary ceremony witnessed by Dalihan Na Tolu. This study addresses two principal issues: (1) the status of pauseang land given to daughters in the Toba Batak indigenous community after divorce; (2) the authority of Dalihan Na Tolu in resolving disputes over pauseang land in the Toba Batak indigenous community after divorce. This study uses a statutory approach to analyze regulations related to legal issues in the research, a conceptual approach based on the thoughts and opinions of legal experts to build legal arguments, and a case study approach to understand cases or events related to the control of pauseang land after divorce. The results indicate that the status of pauseang land given by parents to their daughter after divorce is determined through deliberation and consensus conducted by the Dalihan Na Tolu, taking into account the causes of divorce as a form of customary violation committed by either spouse. The Dalihan Na Tolu, as a customary institution, continues to exist and function effectively in resolving customary disputes, with its decisions consistently obeyed by members of the Toba Batak indigenous community.